2022
DOI: 10.3390/jcm11061555
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Non-Invasive Global Myocardial Work in Asymptomatic Aortic Stenosis

Abstract: This study aimed to evaluate the modification of non-invasive myocardial work (MW) indices related to aortic stenosis (AS) stages of cardiac damage and their prognostic value. The echocardiographic and outcome data of 170 patients, with asymptomatic moderate-to-severe AS and left ventricular ejection fraction (LVEF) ≥50%, and 50 age- and sex-comparable healthy controls were analysed. Primary endpoints were the occurrence of all-cause and cardiovascular death. Increased values of the global work index (GWI), gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
7
1
1
Order By: Relevance
“…Reduced GWI and GCW at follow-up are associated with increased mortality. 82 GWI and GCW positively correlate with aortic regurgitation severity in patients with normal LVEF. 84 GWI threshold of 1285 mm Hg% is a predictor of LV reverse remodeling.…”
Section: Aortic Regurgitationmentioning
confidence: 88%
See 1 more Smart Citation
“…Reduced GWI and GCW at follow-up are associated with increased mortality. 82 GWI and GCW positively correlate with aortic regurgitation severity in patients with normal LVEF. 84 GWI threshold of 1285 mm Hg% is a predictor of LV reverse remodeling.…”
Section: Aortic Regurgitationmentioning
confidence: 88%
“…74 De Rosa et al 81 also found that low-flow, low-gradient AS patients had no improvement in GWI post-TAVR. 81 Lastly, Ilardi et al 82 recently studied the prognostic value of myocardial work in AS patients. They showed increased GWI, GCW, and GWW in AS patients compared with controls and also reported that reduced GWI (hazard ratio [HR], 0.998 [95% CI, 0.997–1.000]; P =0.034) and GCW (HR, 0.998 [95% CI, 0.997–0.999]; P =0.003) measurements after follow-up were significantly associated with excess mortality.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…The GWI has been reported to be a useful diagnostic tool in patients with severe aortic stenosis [9,10]. In a previous 2 of 11 study by Ilardi et al, a GWI ≤ 1951 mmHg% was associated with a higher mortality in moderate-to-severe AS [11]. In addition, the GWI showed an independent association with symptoms in patients with severe AS [12].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, noninvasive measurement of LV myocardial work (MW) has proven to be a valuable method for estimating myocardial performance in AS patients undergoing TAVI [ 24 ]. This tool incorporates echocardiographic strain data, cardiac events timing (from aortic and mitral valve opening and closure), and estimation of LV pressure (derived from systolic blood pressure) in order to derive global work index (GWI), global constructive work (GCW), global wasted work (GWW) and global work efficiency (GWE).…”
Section: Impact Of Tavi On Cardiac Function and Structurementioning
confidence: 99%
“…However, global work indices remained abnormal after the procedure, suggesting an incomplete recovery of the LV function after TAVI [ 25 ] ( Figure 1 ). Moreover, lower values of GCW and GWI at baseline in AS patients have been associated with advanced stages of myocardial disease and with a worse prognosis even after aortic valve replacement [ 24 ].…”
Section: Impact Of Tavi On Cardiac Function and Structurementioning
confidence: 99%